The Interaction Between Epigenetic Changes, EMT, and Exosomes in Predicting Metastasis of Colorectal Cancers (CRC) - Yang, Meiqi; Sun, Mingjun; Zhang, Huijing (Frontiers in Oncology, 2022)
Worldwide, colorectal cancer (CRC) ranks as the third most common malignancy, and the second most deadly with nearly one million attributable deaths in 2020. Metastatic disease is present in nearly 25% of newly diagnosed CRC, and despite advances in chemotherapy, less than 20% will remain alive at 5 years. Epigenetic change plays a key role in the epithelial-to-mesenchymal transition (EMT), which is a crucial phenotype for metastasis and mainly includes DNA methylation, non-coding RNAs (ncRNAs), and N6-methyladenosine (m6A) RNA, seemingly valuable biomarkers in CRCs. For ncRNAs, there exists a “molecular sponge effect” between long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs). The detection of exosomes is a novel method in CRC monitoring, especially for predicting metastasis. There is a close relationship between exosomes and EMT in CRCs. This review summarizes the close relationship between epigenetic changes and EMT in CRCs and emphasizes the crucial function of exosomes in regulating the EMT process.